The use of a two-dimensional electrical resistivity tomography (2D-ERT) as a technique for cadmium determination in cacao crop soils (2020)
Cadmium (Cd) is a non-essential heavy metal naturally occurring in the earth’s crust or due to anthropogenic activity. The presence of this metal in cacao farm soils represents a significant issue as levels are now regulated in products derived from cacao beans (Theobroma cacao L.). Several strategies have been proposed to measure cadmium levels; however, little is known regarding in situ nondestructive and time efficient techniques to analyze Cd contents in both cacao topsoils and subsoils, particularly nearby the root system. Therefore, this research aims to integrate the physical property of soil resistivity to Cd content in cacao soils. Cd hot spots are estimated from resistivity measurements using a two-dimensional electrical resistivity tomography (2D-ERT) technique and correlated to Cd determination using inductively coupled plasma optical emission spectrometry (ICP-OES). To assess the dynamics of soil Cd content the correlation is discussed with other physical chemical parameters of soils (pH, organic matter, Ca, Fe, and P). The study was performed in 27 cacao farms in Colombia. A farm in Santander district proved to have the highest level of Cd using the correlated techniques (2.76 mg·kg−1 Cd and 1815 Ohm·m) followed by farms in Boyacá and Arauca districts (2.6 and 0.66 mg·kg−1 Cd, related to 1616 and 743 Ohm·m, respectively). A high correlation between 2D-ERT and Cd determination (R2 = 0.87) was found. The discussion regarding the soil parameters analyzed suggests that the 2D-ERT technique could be used as a preliminary approach to explore Cd distribution in cacao soils.